EXECUTION OF PENGADILAN TATA USAHA NEGARA JUDGES VERDICT FOR PDAM TIRTA DAROY BANDA ACEH TECHNICAL DIRECTOR DISMISSAL DISPUTE (Judge Case Study Decision Number 05 / B / 2015 / PT.TUN-MDN) - Rispalman Rispalman; Khairani Khairani; Samsul Bahri (Universitas Islam Negeri Ar-Raniry, 2021)
Execution of Pengadilan Tata Usaha Negara (PTUN) judges verdict in some nation administrative dispute resolution practice in Indonesia have not been properly implemented due to the absence of an executorial Instution as well as a strong legal basis lead to weak force power for verdict of the PTUN. Undang-undang Peradilan Tata Usaha Negara also do not explicitly and clearly regulate the issue of force of verdict PTUN and the execution of the verdict really depends on the goodwill of the Tata Usaha Negara Entity or Officials in obeying the law. How was the execution of the PTUN judges verdict? What was the reason for the unexecuted judges verdict? So that we can find out how the judges verdict was executed and the reasons why the judges verdict was not executed. We use sociological research method to search what happened. Executor of a decision required to overcome and minimize the PTUN judges verdict that was not executed as well as improvements to the basis of the Law which is more concrete and forces the execution of PTUN judges verdict so that no party were harmed. Pelaksanaan putusan hakim Pengadilan Tata Usaha Negara dalam praktek penyelesaian sengketa Administrasi negara di Indonesia sebahagiannya belum terlaksana sebagaimana semestinya yang disebabkan ketiadaan lembaga eksekutorial, maupun landasan hukum yang kuat mengakibatkan putusan Pengadilan Tata Usaha Negara tidak mempunyai daya paksa. Undang-undang Peradilan Tata Usaha Negara pun tidak mengatur dengan tegas dan jelas mengenai masalah daya paksa putusan Pengadilan Tata Usaha Negara, sehingga dalam pelaksanaan Putusan benar-benar tergantung pada iktikad baik Badan atau Pejabat Tata Usaha Negara dalam mentaati hukum. Bagaimana pelaksanaan putusan hakim PTUN.? Apa sebab tidak terlaksananya eksekusi putusan hakim tersebut? Sehingga dapat mengetahui bagaimana pelaksanaan putusan hakim dan sebab mengapa tidak terlaksananya putusan hakim tersebut. Dalam meneliti sengekta ini penulis menggunakan metode (Sosiologis research) lebih kepada penelitian lapangan apa yang terjadi, untuk mengatasi dan meminimalisir putusan hakim PTUN yang tidak terlaksana diperlukan adanya eksekutor putusan, serta perbaikan pada landasan Undang-Undang yang bersifat lebih konkrit dan memaksa Pelaksanaan putusan hakim PTUN sehingga tidak ada pihak yang dirugikan.